Recruitment of Thermogenic Fat: Trigger of Fat Burning - Wang, Zhihan; Yu, Xuefeng; Chen, Yong (Frontiers in Endocrinology, 2021)
Brown and beige adipose tissues possess a remarkable capacity of converting energy into heat, which potentially open novel therapeutic perspectives targeting the epidemic of the metabolic syndromes including obesity and type 2 diabetes. These thermogenic fats implement mitochondrial oxidative phosphorylation and uncouple respiration to catabolize fatty acids and glucose, which leads to an increase in energy expenditure. In particular, beige adipocytes arised in white adipose tissue (WAT) display their thermogenic capacity through multical noncanonical mechanisms. This review aims to summarize the general overview of thermogenic fats, especially including the UCP1-independent adaptive thermogenesis and the emerging mechanisms of “beiging”, which may provide more evidences of targeting thermogenic fats to counteract obesity and other metabolic disorders in human.